Aspectos clínicos do enxerto conjuntival 360° e do implante da membrana amniótica criopreservada no tratamento de úlceras de córnea em cães - Ferreira, Gabriel Thadeu Nogueira Martins [UNESP]; Souza, Talita Floering Brêda [UNESP]; Sakamoto, Silmara Sanae [UNESP]; Silva, Tereza Cristina Cardoso [UNESP]; Andrade, Alexandre Lima [UNESP] (Universidade Estadual de Londrina, 2013)
To evaluate the clinical application of implant of the canine cryopreserved amniotic membrane (DMEM plus DMSO 1:1) and 360° conjunctival flap in the treatment of progressive corneal ulceration. 10 dogs of the different breeds, males and females, aging four months to four years old with deep corneal ulceration and different clinical progression were divided in two groups: G1=360° conjunctival graft (n=5) and G2=implant of amniotic membrane, sutured at the edge of the ulcer with epithelial side facing up, associated with the third eyelid flap (n=5). The comparative analysis between groups was: complications, blepharospasm, ocular secretion, corneal vascularization, epithelial defect and corneal opacification in six moments (first emergency care, surgery and 3, 7, 15 and 30 days of postoperative). Without epithelial defect was evaluated quality of the scar. It was used score scale for subjective to qualify of the ocular signs. In G1, it was observed the non-adherence of the conjunctival graft to the ulcer (n=2), dehiscence of the suture (n=2), anterior synechia (n=2) and intense chemosis (n=1). In G2, it was not observed these complications. It was not significant difference between the groups to others ocular parameters, but it was different among the start and end moments of the same groups (ocular secretion, corneal vascularization, epithelial defect). The corneal opacity was more intense in G1. According to the clinical results, the cryopreserved amniotic membrane implant proved to be as effective in the corneal ulceration in comparison to the 360° conjunctival flap, because probably, the membrane promoted a trophic support for epithelialization, anti-inflamatory effect associated with important to the end result phenotype.
Clinical aspects of the 360° conjunctival graft and amniotic membrane cryopreserved transplantation in corneal ulcers in dogs
Keywords: Amnion; Cornea; Corneal ulcer; Dogs; Homologous; Tissue transplantation; Transplantation